The Physics of Metrology All about Instruments: From Trundle Wheels to Atomic Clocks - Hebra, Alexius J.; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
Conceived as a reference manual for practicing engineers, instrument designers, service technicians and engineering students. The related fields of physics, mechanics and mathematics are frequently incorporated to enhance the understanding of the subject matter. Historical anecdotes as far back as Hellenistic times to modern scientists help illustrate in an entertaining manner ideas ranging from impractical inventions in history to those that have changed our lives.
The measurement of length -- Angles and arcs -- Clocks and the measurement of time -- Velocity and acceleration -- Force, mass, weight, and torque -- Vibrations -- Thermodynamics -- Pressure -- Density of solids, liquids, and gases -- Light and radiation -- Acoustics -- Electrical and electronic instruments -- Automation $1 (BInstruments that think.s
Keywords: Physics; Engineering; Mechanical engineering; Control engineering systems; Electronics; Physics; Measurement Science and Instrumentation; Mechanical Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Electronics and Microelectronics, Instrumentation; Engineering, general; Control , Robotics, Mechatronics